Applicability of solar desiccant cooling systems in Algerian Sahara: Experimental investigation of flat plate collectors - Labed, Adnane; Rouag, Amar; Benchabane, Adel; Moummi, Noureddine; Zerouali, Mohammed (Journal of Applied Engineering Science & Technology; Vol 1 No 2 (2015), 2015)
The increasing interest in the development of solar cooling technologies to their various economic and impressive environmental benefits, conducted us to study the feasibility of solar desiccant cooling systems in Algerian Sahara, particularly in the region of Biskra. Thus, we present in this paper, the results of an experimental investigation of solar flat plate collectors (FPCs) to test and estimate their heat regeneration capacity for solid desiccant cooling applications. The applicability of both Pennington and Dunkle cycles taking into account the effects of some parameters such as outdoor humidity and temperature and hot air temperature required to regenerate the desiccant wheel have been studied. From the psychrometric analysis, it was found that the Dunkle cycle is suitable in warm and semiarid climate. In addition, this study has allowed us to show that the temperature achieved by the flat plate solar air heaters in a large band of air flow rate can satisfy the energy needs for the dehumidification in desiccant cooling systems. Hot water produced by the solar water heaters and the stored one are in the operating temperature gap of the system (50-80 °C).
Keywords: Air conditioning, Desiccant cooling, Sorption, Solar collectors, Saharan climate